Islamic Foreign Policy Principles Derived from the Covenants of Prophet Muhammad - Abubakar Salati; Mashood Saad; JAMIU SALIU; Daud Ahmad Attejaany; Sikrullah Shehu Abdulqadir (Journal of Islamic Political Studies)
Countries often establish principles to guide their foreign policies, often prioritizing their own interests over those of others. This paper will explore Islamic principles of foreign policy, drawing from the covenants of Prophet Muhammad. The Prophet’s letters to kings and leaders are considered pivotal in shaping the foreign policy of the early Islamic state. These letters emphasized the universality of his mission, underscoring its significance in both religious and political contexts. From this historical heritage, thirteen universal principles have been derived that could serve as an alternative to current foreign policy norms. Rooted in justice and equity, these principles promote an egalitarian society and are beneficial not only for Muslims but for humanity as a whole. This study adopts a library-based and analytical methodology to present these principles.